Comparison of occupational burnout scores among medical residents and their correlation with dimensions of TCI questionnaire - Haghshenas, Mandana (Med J Islam Repub Iran, 2019)
Background: The present study was conducted to compare occupational burnout scores and determine their correlation with different dimensions of Temperament and Character Inventory (TCI) questionnaire among psychiatry, internal medicine, and surgery residents during the academic year 2013-14. Methods: In this cross sectional analytical study, 201 residents were recruited. Colinger's 125-item TCI and Maslach's Burnout Inventory were completed by residents. The mean severity of burnout and the mean scores in the subgroups of temperament and character were compared between the 3 groups of residents, and the correlations were calculated. Data were analyzed using SPSS software version 16. Also, A 2-sided p value of less than 0.05 was considered significant. Results: A significant positive correlation was found between severity of burnout and harm avoidance in internal medicine residents (r=0.7, p<0.001). Also, a significant correlation was found between severity of burnout and self-directedness in surgery residents (r=0.5, p=0.003), self-transcendence in internal medicine residents (r=0.04, p=0.009), and persistence in internal medicine (r=0.17, p=0.003) and surgery residents (r=0.10, p=0.004). A significant correlation was found between frequency of burnout and harm avoidance in internal medicine residents (r=0.6, p=0.001), self-directedness in surgery residents (r=0.9, p<0.001), persistence in surgery (r=0.14, p<0.001) and psychiatry residents (r=0.19, p<0.001), and finally self-transcendence in internal medicine residents (r=0.6, p<0.001). Conclusion: Dimensions of character were different among surgery, internal medicine, and psychiatry residents. Likewise, the severity of burnout was different among them according to personality traits. Occupational burnout appears to be less if personality traits match the chosen specialty.